2021
DOI: 10.24996/ijs.2021.si.1.42
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties in Developing the Diagnostic Competence of Nursing Students At My Youssef Hospital in Casablanca: Descriptive Study

Abstract: This descriptive research aims atidentifying the difficulties encountered by nursing students in the development of nursing diagnostic skills. The data collection was carried out using a direct questionnaire with 62 students in My Youssef’s hospital in Casablanca. The results of the study list a set of failures related to the training of nurses. This training focuses mainly on the acquisition of knowledge; it is not aimed to the development of the real skill.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…In the field of health sciences, students are able to memorize the clinical manife stations of diseases but are unable to solve a sick person's problem (Harouchi, 2010). In this sense, Darraj, Gourja, Faiq, and Belaaouad (2021) have demonstrated that there is a gap between nursing education goals aimed at learning and skill development in the nursing field and implementing this approach in educational settings. Darraj et al (2021) also pointed out that, at best, young people are 'savants' when they leave school.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the field of health sciences, students are able to memorize the clinical manife stations of diseases but are unable to solve a sick person's problem (Harouchi, 2010). In this sense, Darraj, Gourja, Faiq, and Belaaouad (2021) have demonstrated that there is a gap between nursing education goals aimed at learning and skill development in the nursing field and implementing this approach in educational settings. Darraj et al (2021) also pointed out that, at best, young people are 'savants' when they leave school.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, Darraj, Gourja, Faiq, and Belaaouad (2021) have demonstrated that there is a gap between nursing education goals aimed at learning and skill development in the nursing field and implementing this approach in educational settings. Darraj et al (2021) also pointed out that, at best, young people are 'savants' when they leave school. They are not necessarily competent.…”
Section: Introductionmentioning
confidence: 99%